Improved coagulation in bleeding disorders by Non-Anticoagulant Sulfated Polysaccharides (NASP) - Liu, Tongyao; Scallan, Ciaran D.; Broze, George J., Jr.; Patarroyo-White, Susanna; Pierce, Glenn F.; Johnson, Kirk W. (Thrombosis and Haemostasis, 2006)
Additional therapeutic options are needed for patients with bleeding disorders such as hemophilia A, hemophilia B, severe von Willebrand disease, and other rare factor deficiencies. A novel approach to improve coagulation in such clotting disorders has been identified that, parodoxically, involves heparinlike sulfated polysaccharides.Select molecules of this broad class are largely devoid of anticoagulant activity and are here denoted Non-Anticoagulant Sulfated Polysaccharides (NASPs).A mechanism involving blockade of the extrinsic pathway downregulator,Tissue Factor Pathway Inhibitor (TFPI) by NASPs, was conceived as an approach for improving procoagulant behavior in hemophilic settings.A subset of NASPs, including pentosan polysulfate (PPS) and fucoidan inhibited both full-length and Kunitz 1 and 2 (K1K2) TFPI and, at concentrations from 4-500 nM, improved (i.e. accelerated) the clotting time of human hemophilia A and hemophilia B plasmas or plasma with reduced factor VII levels when tested in dilute prothrombin time (dPT) assays. Fucoidan did not reduce normal plasma APTT times implying specificity for extrinsic pathway control. Improved hemostasis in vivo was observed in mice with hemophilias A orB following low dose subcutaneous administration of PPS or fucoidan, or a combination of NASP plus factor supplement. Increased survival of factor deficient mice following a bleeding challenge was observed. Accordingly, administration of select NASP(s), via mechanism(s) not fully understood, represents a unique means of improving coagulation in bleeding disorders.
Keywords: Hemophilia; sulfated polysaccharides; fucoidan; TFPI; coagulation